The unsinkable Molly Brown [videorecording (DVD)] - Walters, Charles, 1911-1982; Reynolds, Debbie; Presnell, Harve; Begley, Ed, 1901-1970; Kruschen, Jack, 1922-2002; Baddeley, Hermione, 1908-1986; Morris, Richard, 1924-1996 (Warner Home Video, 2000)
Molly, a poor, uneducated young woman, leaves her mountain cabin home in search of a rich husband and a better life. She finds both in Leadville Johnny Brown as she strikes it lucky and he strikes gold.